Joint Sensor Selection and Observer Design for Positive Systems via Mixed-Integer Semidefinite Programming - Gagliardi, Gianfranco; Torchiaro, Franco Angelo; Casavola, Alessandro (IEEE control systems letters, 2024)
This letter addresses the joint sensor selection and observer design problem for positive systems. The proposed methodology leverages Mixed-Integer Semidefinite Programming (MISDP) techniques, providing a rigorous and systematic framework for optimizing the selection of sensors and the design of the corresponding optimal L_{1} observer in a unified manner. This configuration not only enables the reconstruction of the full state with a minimal number of sensors but also optimizes specific state reconstruction metrics with the objective of enhancing the efficiency, reliability, and robustness of the scheme. The theoretical validation of the sensor placement's optimality is also provided and its relevance is demonstrated through numerical simulations and comparisons with H_{2} observers.